2018
DOI: 10.1002/ijc.31901
|View full text |Cite
|
Sign up to set email alerts
|

Use of terbinafine and risk of death in patients with prostate cancer: A population‐based cohort study

Abstract: Terbinafine is used for the treatment of several superficial fungal infections. In silico analyses and animal models suggest that terbinafine might have an anti‐tumor effect. We aimed to explore whether subsequent administration of terbinafine might be associated with a lower mortality rate in patients with prostate cancer. We identified patients diagnosed with prostate cancer between July 2005 and December 2014 from the Swedish Cancer Registry, and linked them to the Swedish Prescribed Drug Register to ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…We also demonstrate that competitive inhibition of SQLE with the FDA- and EMA-approved drug terbinafine reduces tumour growth in a murine PCa model and provide preliminary evidence on the efficacy of the drug in PCa patients. Interestingly, a recent population-based cohort study reported an up to 47% reduction in the risk of disease-specific death for PCa patients receiving oral terbinafine treatment 54 . Based on these data, we believe that SQLE could be a target for the treatment of advanced PCa and that inhibitors of SQLE should be evaluated in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrate that competitive inhibition of SQLE with the FDA- and EMA-approved drug terbinafine reduces tumour growth in a murine PCa model and provide preliminary evidence on the efficacy of the drug in PCa patients. Interestingly, a recent population-based cohort study reported an up to 47% reduction in the risk of disease-specific death for PCa patients receiving oral terbinafine treatment 54 . Based on these data, we believe that SQLE could be a target for the treatment of advanced PCa and that inhibitors of SQLE should be evaluated in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Terbinafine is an antifungal drug; studies on this drug indicate that it blocks the proliferation of human cancer cells, regulates tumor progression, influences angiogenesis and, when administered via systemic routes, reduces PC mortality by 47% [ 45 ]. Furthermore, terbinafine is involved in p53 signaling, triggering apoptosis and can inhibit DNA synthesis to prevent tumor growth and decrease the synthesis of steroids, including cholesterol, which is usually produced in high amounts in cancer cells [ 45 ]. However, it is still not known for sure which mechanism of action allows terbinafine to be a good candidate for drug repurposing in PC, as this drug inhibits squalene monooxygenase, which is a fundamental enzyme in cholesterol synthesis [ 45 ].…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%
“…Allylamines, as pioneers of SQLE inhibitors, were investigated for antitumor therapy. In a retrospective cohort study, patients with prostate cancer receiving systemic use of terbinafine had a decreased risk of overall death (HR=0.64; 95% CI, 0.52–0.77) and a decreased risk of death from prostate cancer (HR, 0.64; 95% CI, 0.52–0.77), while the topical use of terbinafine seemed not to bring survival benefits ( 90 ). Recently, four patients with rapidly progressive end-stage metastatic prostate cancer after multiple prior treatment modalities, excluding ADT and radiation, were off-label administered terbinafine orally.…”
Section: Sqle-targeted Therapeutic Strategies For Cancer Treatmentmentioning
confidence: 99%